A case study for late Archean and Proterozoic biogeochemical iron‐ and sulphur cycling in a modern habitat—the Arvadi Spring. Issue 4 (9th June 2018) - Koeksoy, Elif; Halama, Maximilian; Hagemann, Nikolas; Weigold, Pascal R.; Laufer, Katja; Kleindienst, Sara; Byrne, James M.; Sundman, Anneli; Hanselmann, Kurt; Halevy, Itay; Schoenberg, Ronny; Konhauser, Kurt O.; et al.
Abstract: As a consequence of Earth's surface oxygenation, ocean geochemistry changed from ferruginous (iron(II)‐rich) into more complex ferro‐euxinic (iron(II)‐sulphide‐rich) conditions during the Paleoproterozoic. This transition must have had profound implications for the Proterozoic microbial community that existed within the ocean water and bottom sediment; in particular, iron‐oxidizing bacteria likely had to compete with emerging sulphur‐metabolizers. However, the nature of their coexistence and interaction remains speculative. Here, we present geochemical and microbiological data from the Arvadi Spring in the eastern Swiss Alps, a modern model habitat for ferro‐euxinic transition zones in late Archean and Proterozoic oceans during high‐oxygen intervals, which enables us to reconstruct the microbial community structure in respective settings for this geological era. The spring water is oxygen‐saturated but still contains relatively elevated concentrations of dissolved iron(II) (17.2 ± 2.8 μM) and sulphide (2.5 ± 0.2 μM) with simultaneously high concentrations of sulphate (8.3 ± 0.04 mM). Solids consisting of quartz, calcite, dolomite and iron(III) oxyhydroxide minerals as well as sulphur‐containing particles, presumably elemental S 0, cover the spring sediment. Cultivation‐based most probable number counts revealed microaerophilic iron(II)‐oxidizers and sulphide‐oxidizers to represent the largest fraction of iron‐ and sulphur‐metabolizers in the spring, coexisting with less abundant iron(III)‐reducers, sulphate‐reducers and phototrophic and nitrate‐reducing iron(II)‐oxidizers. 16S rRNA gene 454 pyrosequencing showed sulphide‐oxidizing Thiothrix species to be the dominating genus, supporting the results from our cultivation‐based assessment. Collectively, our results suggest that anaerobic and microaerophilic iron‐ and sulphur‐metabolizers could have coexisted in oxygenated ferro‐sulphidic transition zones of late Archean and Proterozoic oceans, where they would have sustained continuous cycling of iron and sulphur compounds.